Oils and fats: detection methods for evaluation, chemical characterization, and diagnosis of their antioxidant effects (Journal of the College of Basic Education, 2025)
introduction: Given the importance of oils and fats and their close association with human health, it is essential to study and describe their basic components to understand their biological and chemical properties. Methods: This study focused on the characterization of “Sunflower oil (Al-Dar)", virgin olive oil "Kul Al-Afiyah Oil" , and “Animal Fat – Abu Ghraib”. Using ultraviolet-visible (UV-Vis), Fourier-transform infrared (FTIR), and gas chromatography-mass spectrometry (GC-MS), and to study their antioxidant properties. Results:Wavelengths in the range of 200 to 400 nm were investigated, and the absorbance of the selected samples was found at wavelengths of 278, 290, and 265 nm, respectively. Spectroscopic analysis was used to identify functional groups on the surfaces of sunflower and olive oils. Fourier-transform infrared. Spectroscopy with component analysis was used to identify different functional groups. By examining the absorption peaks between 4000 and 500 cm¹, animal fats performed better when measuring their effectiveness in preventing oxidation. "Animal Fat – Abu Ghraib" recorded the highest free radical scavenging capacity, reaching 54.5695%, while virgin olive oil "Kul Al-Afiyah Oil” recorded 22.9139 %. And “Sunflower oil (Al-Dar)“recorded 4.23841% .The results indicated that the selected samples contained biologically active chemical compounds; however, animal fat exhibited significantly higher antioxidant properties.